2015
DOI: 10.1007/s00420-015-1055-9
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and sickness presenteeism: cross-sectional and prospective associations in a 2-year follow-up study

Abstract: This study provides indications of a significant relationship between exposure to frequent workplace bullying and SP, although causal connections could not be established. Methodological and theoretical considerations about study findings are provided, which could be of benefit to future studies examining the impact of being a target of workplace bullying on SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 80 publications
1
32
1
3
Order By: Relevance
“…They might be excluded from important decisions, or they might be deprived of their original work tasks (Conway et al, 2016). Conway et al (2016) also find that frequently bullied individuals more often attend work even though they are ill compared to non-bullied individuals; however, the significance of the results disappears once they condition on baseline presenteeism. 39 The questionnaire asks respondents to state how many days they went to work during the past year.…”
Section: Presenteeismmentioning
confidence: 81%
See 1 more Smart Citation
“…They might be excluded from important decisions, or they might be deprived of their original work tasks (Conway et al, 2016). Conway et al (2016) also find that frequently bullied individuals more often attend work even though they are ill compared to non-bullied individuals; however, the significance of the results disappears once they condition on baseline presenteeism. 39 The questionnaire asks respondents to state how many days they went to work during the past year.…”
Section: Presenteeismmentioning
confidence: 81%
“…According to the results, this does not appear to be the case. Based on conservation of resources theory, Conway et al (2016) argue that targets of bullying 38 Results available from the authors upon request.…”
Section: Public Sector Employeesmentioning
confidence: 99%
“…These studies may be classified into two groups: (a) those based on the European Working Conditions Survey (EWCS), where the question used is “over the past 12 months did you work when you were sick?,” the answer being dichotomous (no/yes) . Some studies exclusively analyze this question, while others additionally take a second question into account, namely “if yes, how many working days?” The versions of the Korean Working Conditions Survey also use a dichotomous question similar to that of the EWCS, although with slightly different formulations depending on survey version; (b) those studies which use exactly the same question used by Aronsson, “has it happened over the previous 12 months that you have gone to work despite feeling that you really should have taken sick leave due to your state of health?,” as well as some other studies which use minor modifications of this question or other similar ones where the formulation explicitly investigates “how many times…” or “how many days…”…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on bullying and presenteeism have reported that frequent (i.e. daily or weekly) exposure to workplace bullying was associated with higher reporting of sickness presenteeism in the preceding year (Conway et al 2016). In another study it was found that negative relational experiences such as being exposed to harassement, discrimination and abuse were positively related to presenteeism (Miraglia and Johns 2016).…”
Section: Sickness Absenteeism Presenteeism and Bullyingmentioning
confidence: 89%